Why Software Fails - We waste billions of dollars each year on entirely preventable mistakes - and Robert N., Charette (IEEE Spectrum, 2005)
We waste billions of dollars each year on entirely preventable mistakes. The biggest tragedy is that software failure is for the most part predictable and avoidable. Unfortunately, most organizations don't see preventing failure as an urgent matter, even though that view risks harming the organization and maybe even destroying it. Understanding why this attitude persists is not just an academic exercise; it has tremendous implications for business and society.